Edward Willis papers - Willis, Edward, 1834-1910.
Correspondence, ledger, memorandum books, requisition books, newspaper clippings, printed material, drawings, photographs, and other papers relating primarily to Willis's service as chief quartermaster of G.T. Beauregard's division in the Confederate Army. Documents defensive operations along the South Carolina and Georgia coasts, the siege of Petersburg, and movement of troops in Alabama, Georgia, and Mississippi.
Confederate Army officer and merchant of Charleston, S.C.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beauregard, G. T. -- 1818-1893.; Confederate States of America. -- Army -- Supplies and stores; Alabama -- History -- Civil War, 1861-1865 -- Campaigns; Georgia -- History -- Civil War, 1861-1865 -- Campaigns; Mississippi -- History -- Civil War, 1861-1865 -- Campaigns; Petersburg (Va.) -- History -- Siege, 1864-1865.; South Carolina -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers, Confederate; Merchants